Respon Terhadap Covid-19, Tanaman Hias, dan Status Sosial - Nur Safitra fitra; Anwar Anwar (Emik, 2021)
Covid-19 which has hit Indonesia since March 2021, which not only affects public health but also has an impact on almost all aspects of human life. Various efforts have been made, both medical and non-medical. The new contribution in this article is farming in time of pandemic Covid-19, especially ornamental plants, as self-healing and how ornamental plants have become symbols of social status. Using qualitative approach, this research was carried out in Soppeng Regency, as a district whose government issued a specific policy in relation to anticipating the impact of Covid-19, namely farming. There were ten people who participated in this study which varied based on age (between 22 and 50 years), occupation [three housewives (one of whom was a daily laborer), two farmers and a trader, an office worker, and a seamstress]. Data was collected through observation and in-depth interviews. The public's initial response regarding the Covid-19 pandemic was divided into two, namely those who did not believe in the existence of Covid-19 and those who believed in the existence of Covid-19. The first group tends to be indifferent to the situation, while the second uses various methods to prevent the transmission of Covid-19 and overcome boredom, starting from maintaining body immunity, complying with health protocols, to farming. Among the health protocols launched by the government, social distancing is the most difficult to implement, so it tends to be ignored. Although farming activities during the Covid-19 pandemic period are not the hallmark of the Soppeng community, what makes it unique is that the government made a policy through Surat Edaran Bupati No. 521/497/Pertanian/IV/2020, regarding the Appeal for the Utilization of Yard Land by Planting Horticultural Crops (vegetables/tubers/fruits/toga) in anticipation of the impact caused by Covid-19. Planting is already a fast growing trend. Ownership of certain plants became a status symbol. The relationship between the two is caused by three factors, namely: planting ornamental plants requires capital to maintain them; there are types of ornamental plants that are popular and relatively expensive; and ornamental plants have many devotees. The more expensive the ownership of the ornamental plants, the higher the status. Expensive ornamental plants are posted on social media, and this triggers others to have such posted plants. Social media has become a competition event for ornamental plant ownership.